2013
DOI: 10.1590/0037-8682-0007-2012
|View full text |Cite
|
Sign up to set email alerts
|

Serologic assessment of yellow fever immunity in the rural population of a yellow fever-endemic area in Central Brazil

Abstract: Introduction:The yellow fever epidemic that occurred in 1972/73 in Central Brazil surprised the majority of the population unprotected. A clinical-epidemiological survey conducted at that time in the rural area of 19 municipalities found that the highest (13.8%) number of disease cases were present in the municipality of Luziânia, State of Goiás. Methods: Thirty-eight years later, a new seroepidemiological survey was conducted with the aim of assessing the degree of immune protection of the rural population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…There was a strong infl uence of rainfall on the annual cycle of the species of Sabethes and Haemagogus, which have eggs that are very resistant to desiccation and sometimes require repeated contact with water to hatch 20 . Similar situations related to these genera have been described in Mato Grosso 31 58 , entomological monitoring is recommended in the BNP and in other areas that are susceptible to the transmission of the YF virus. We emphasize that the BNP is located 10km from the center of Brasília and 2km from the Setor Habitacional Noroeste, where many apartments are being constructed.…”
Section: Discussionmentioning
confidence: 64%
“…There was a strong infl uence of rainfall on the annual cycle of the species of Sabethes and Haemagogus, which have eggs that are very resistant to desiccation and sometimes require repeated contact with water to hatch 20 . Similar situations related to these genera have been described in Mato Grosso 31 58 , entomological monitoring is recommended in the BNP and in other areas that are susceptible to the transmission of the YF virus. We emphasize that the BNP is located 10km from the center of Brasília and 2km from the Setor Habitacional Noroeste, where many apartments are being constructed.…”
Section: Discussionmentioning
confidence: 64%
“…It remains unclear how mouse protection experiments relate to protective immunity in humans since an early study demonstrated that mice could be protected by transfer of immune human serum that was non-protective in the more clinically relevant rhesus macaque model [35]. Of the remaining 9 studies that measured neutralizing titers at ≥10 years after YFV-17D vaccination, 4 were performed in endemic countries [13,40,41,45] and 5 were performed in non-endemic countries (references [27,28,30,46] and an unpublished analysis of CDC Arbovirus laboratory testing). When stratified into these two groups, 97.6% (359/368) of subjects from YFV-endemic areas maintained detectable neutralizing antibodies whereas only 83.7% (264/337) of subjects who lived in non-endemic countries remained seropositive.…”
Section: Yellow Fever Correlate Of Immunity and Duration Of Antibomentioning
confidence: 99%
“…Os sintomas da Febre Amarela são classificados de acordo com o quadro clínico da doença, que pode ser leve, moderado e grave. As formas leve, são mais frequentes em crianças e adultos que já entraram em contato com o vírus anteriormente, seja pela imunização ativa ou passiva, apresentando sintomas que se restringem a astenia, cefaléia e febre (MACHADO et al, 2013). O quadro da doença na sua forma moderada é de curta duração, apresentando uma sintomatologia que pode ser confundida com outras doenças infecciosas.…”
Section: Resultados E Discussõesunclassified
“…A doença se caracteriza por apresentar alguns sintomas que se confundem a outras doenças virulentas, como febre alta, icterícia, astenia, cefaleia, artralgias, náuseas, vômitos, entre outras (GOLDMAN; BENNETT, 2011). Essas características podem está relacionadas com suas formas de manifestação que podem ser leve, moderada ou grave (MACHADO et al, 2013). No Brasil, a Febre Amarela causou a morte de milhares de pessoas nas últimas epidemias, que até então eram consideradas controladas, com algumas ocorrências isoladas ao longo dos anos.…”
Section: Febre Amarelaunclassified